2016
DOI: 10.5714/cl.2016.19.023
|View full text |Cite
|
Sign up to set email alerts
|

Carbon rich fly ash and their nanostructures

Abstract: Carbon rich fly ash was recently reported to have compositions that are ideal for use as a precursor and catalyst for carbon nanotube growth. This fly ash powder is mostly composed of pure carbon, predominantly present as sp 2 . In this work, the effect of sonication time on the morphology and structural properties of carbon rich fly ash particles is reported. The obtained results show that ultrasound treatment is an effective tool for producing ultrafine particles/fragments with higher porosity, which might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Fly ash was obtained from an electric power plant in Jeddah. The original fly ash contains impurity elements of Na, Al, V, Fe, Ni, Cu, Zn, S, Si, etc. , Except for S and Si, metal elements exist in oxidized materials or salts which can be easily removed by water and acid etching. First of all, impurities in large particles were removed by sieving with a 50 mesh sieve.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fly ash was obtained from an electric power plant in Jeddah. The original fly ash contains impurity elements of Na, Al, V, Fe, Ni, Cu, Zn, S, Si, etc. , Except for S and Si, metal elements exist in oxidized materials or salts which can be easily removed by water and acid etching. First of all, impurities in large particles were removed by sieving with a 50 mesh sieve.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Through simple purification, FAC can be used to produce high-quality functional carbon materials. 5,6 During the severe combustion condition, the FAC forms an amorphous short-range ordered microcrystalline structure, which is more suitable for anode material in alkali metal-ion batteries compared with the commercial graphite. 7 It is well known that the first commercial lithium-ion battery (LIB) was assembled using an amorphous carbon anode.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiO 2 NPs also mitigated salt stress in Glycine max L. by enhancing the production of enzymatic and non-enzymatic substances (Farhangi-Abriz and Torabian 2018). Oil fly ash waste is found to be a potential source of carbon nanostructures for the synthesis of carbon nanostructures (Salah et al 2016;Al Malack et al 2013;Li et al 2021;Wu et al 2022). Numerous studies have tried to obtain nanostructured carbon through using high-energy ball milling technology as an ecofriendly method of producing carbon nanostructures (Salah et al 2021;Alluqmani et al 2021a, b;Alluqmani et al 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…For developed nanomaterials, high-energy ball milling has proven to be an effective method for manufacturing nanocrystalline powders 12 . Recently, many studies have reported successful realization of carbon nanostructures engineered from oil fly ash waste by high-energy ball-milling techniques, with sizes ranging from 100 to 20 nm for agglomerated clusters; these provide highly graphitic compositions, large specific surface areas, porosity, nontoxicity, strength, and scattering responses, all of which are promising results 13 16 . Moreover, Numan et al successfully used a sonication method to reduce the sizes of oil fly ash particles to a few nanometres 13 .…”
Section: Introductionmentioning
confidence: 99%